Internet Gaming Disorder: An Emergent Health Issue for Men - Kevin H. Chen MN-NP, NP(F), CSCS; John L. Oliffe PhD, RN; Mary T. Kelly MA (American Journal of Men's Health, 2018)
Internet gaming is a legitimate leisure activity worldwide; however, there are emerging concerns that vast numbers of gamers are becoming addicted. In 2013, the American Psychiatric Association (APA) classified Internet Gaming Disorder (IGD) as a condition warranting more clinical research ahead of formalizing it as a mental disorder. Proposed as a behavioral addiction, IGD shares many similarities in both physical and psychosocial manifestations with substance use disorder, including cerebral changes on functional magnetic resonance imaging (fMRI). Among the gaming population, compared to females, adolescent and adult males demonstrate far more addictive internet gaming use in terms of screen hours, craving, and negative impacts on health, which have, in isolated incidents, also caused death. The current article draws findings from a scoping review of literature related to IGD as a means to raising awareness about an emergent men’s health issue. Included are three themes: (a) unveiling the nature, impacts and symptoms of IGD; (b) conceptualizing IGD through neuroscience; and (c) treatment approaches to IGD. Afforded by these themes is an overview and synthesis of the existing literature regarding IGD as a means of providing direction for much needed research on gaming addiction and orientating primary care providers (PCPs) to the specificities of IGD in men’s health. The findings are applied to a discussion of the connections between IGD and masculinity and the importance of recognizing how behaviors such as social isolation and game immersion can be maladaptive coping strategies for males.